E-Service Quality, E-Wallet Dan Kepercayaan Terhadap Minat Beli Pada Pengguna Pembayaran Non Tunai Aplikasi Shopee - Steven, Jacob; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research is a quantitative study with a causal relationship to determine the immediate effect of e-serservice quality, e-wall, trust in buying interest and knowing the indirect influence, e-s service quality, e-wall, trust in non-Shopee app cash payment interest. Data collection was conducted by the method of collecting information through a survey with a questionnaire. The population in this study were someone who had used Shopee, regularly using Shopee, domiciled in Jakarta, a minimum of 17 years old. The sampling method used is non-possibility sampling using purposed sampling technique. Based on the results of the study, 4 hypotheses can be accepted, namely e-sservice quality affects trust, e-wall quality effects of purchasing interest and e-wallt have effect interest in buying and 1 hypothesis cannot be accepted by interest in purchasing interests, Contributions from this study e-servis quality and e-walling interest in purchasing interest. Keywords: E-Service Quality, E-Wallet, Trust, Buying Interest